2015
DOI: 10.1186/s40557-015-0081-0
|View full text |Cite
|
Sign up to set email alerts
|

The association between shift work and depression in hotel workers

Abstract: BackgroundShift work is vital in hotel businesses as these businesses run 24 h daily regardless of holidays to accommodate customers. The number of shift workers in hotel businesses is expected to increase consistently and it is crucial to study the impact of shift work on hotel workers’ mental health. This study, therefore, aims to examine the association between depression and shift work in hotel workers. It especially focuses on investigating whether there is a difference in how closely these two are relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…This relationship is not restricted to the healthcare industry. It has previously been found in other industries, including oil rig workers (Waage et al., ), factory workers (Kaneko et al., ) and hotel workers (Moon, Lee, Lee, Lee, & Kim, ). However, previous research on SWD has been inconsistent due to the variability in parameters used to measure shift work‐related sleep impairment, such as excessive sleepiness, sleep latency, sleep duration and insomnia symptoms, making results hard to compare.…”
Section: Discussionmentioning
confidence: 62%
“…This relationship is not restricted to the healthcare industry. It has previously been found in other industries, including oil rig workers (Waage et al., ), factory workers (Kaneko et al., ) and hotel workers (Moon, Lee, Lee, Lee, & Kim, ). However, previous research on SWD has been inconsistent due to the variability in parameters used to measure shift work‐related sleep impairment, such as excessive sleepiness, sleep latency, sleep duration and insomnia symptoms, making results hard to compare.…”
Section: Discussionmentioning
confidence: 62%
“…No association was reported between shift work and MDD in a French study 69 . If all types of depression are combined, then a clear association emerges between shift work and depression 13,[71][72][73] . A meta-analysis of 11 studies concluded that night shift workers are 40% more likely to develop depression relative to daytime workers 13 .…”
Section: Circadian Rhythm Disruption and Major Depressive Disordermentioning
confidence: 99%
“…For example, compared to those working regular daytime hours, three shifts workers are more likely to suffer from depression (Moon, Lee, Lee, Lee, & Kim, 2015;Waage et al, 2014). For example, compared to those working regular daytime hours, three shifts workers are more likely to suffer from depression (Moon, Lee, Lee, Lee, & Kim, 2015;Waage et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…As well as implications for physical health, shift workers are also at risk of lower mental well-being. For example, compared to those working regular daytime hours, three shifts workers are more likely to suffer from depression (Moon, Lee, Lee, Lee, & Kim, 2015;Waage et al, 2014). This is likely due to the disruption in their circadian rhythms owing to their irregular sleep-wake cycle (Au & Reece, 2017).…”
Section: Introductionmentioning
confidence: 99%